2016
DOI: 10.1364/oe.24.009237
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental research of supercontinuum generation in an ytterbium-doped fiber amplifier

Abstract: The theoretical research of supercontinuum (SC) generation in a fiber amplifier system has been seldom reported. For the purpose of further understanding the mechanism of SC generation in fiber amplifiers, we propose a combined numerical model of the laser rate equations and the generalized non-linear Schrödinger equation to simulate the amplification of 1060 nm picosecond pulses and their spectral broadening in an ytterbium-doped fiber amplifier. The calculation results of this model are compared with the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Recently, there have been a number of experiments and simulations demonstrating SC generation in the AD region of PCFs [10][11][12][13][14]. Li et al reported a study on the coherency of SC spectra of a tapered fluorotel-lurite micro-structured fiber in wavelength range of 1.4 to 4 µm with pumped wavelength of 1980 nm [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been a number of experiments and simulations demonstrating SC generation in the AD region of PCFs [10][11][12][13][14]. Li et al reported a study on the coherency of SC spectra of a tapered fluorotel-lurite micro-structured fiber in wavelength range of 1.4 to 4 µm with pumped wavelength of 1980 nm [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the number of pulses depends on the total gain of the amplifier as well as on the input pulse width. C. Lei et al numerically investigated SC generation in a nonlinear ytterbium-doped fiber amplifier with an AD region [14]. By pumping at the wavelength of 1060 nm and an output power of 300 W, a broad SC spectrum was obtained in the wavelength range from 1000 nm-2000 nm.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the rate-equationbased approach utilized in [9] might be no longer appropriate enough for such extremely fast nonlinear interactions in the AD regime. We note that to date only a handful of numerical or theoretical studies have been carried out on analyzing novel characteristic aspects of SCG in active fibers in the AD regime [12], [18]- [20]. In particular, Lei et al reported that SCG in a Yb-doped fiber (YDF) with AD can be modeled by combining the well-known rate equation and the nonlinear Schrödinger equation (NLSE) when excited by ps pulses [12].…”
Section: Introductionmentioning
confidence: 99%
“…We note that to date only a handful of numerical or theoretical studies have been carried out on analyzing novel characteristic aspects of SCG in active fibers in the AD regime [12], [18]- [20]. In particular, Lei et al reported that SCG in a Yb-doped fiber (YDF) with AD can be modeled by combining the well-known rate equation and the nonlinear Schrödinger equation (NLSE) when excited by ps pulses [12]. However, it remains questionable to apply the given method to the rigorous analysis of SCG in the sub-100-fs regime, because the interactions between active ions and sub-100-fs ultrafast solitons, which inevitably arise during the SCG process in the AD regime, cannot be modeled properly based on the standard rate equation method.…”
Section: Introductionmentioning
confidence: 99%
“…However, the spectrum is not particularly flat, as it is limited by the length of the fiber and the low Raman gain coefficient, as discussed in Ref. [20].…”
Section: Introductionmentioning
confidence: 99%